2018
DOI: 10.1039/c8tx00041g
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses of hyaluronic acid-coated chitosan nanoparticles

Abstract: In recent years, nanotechnology has been proven to offer promising biomedical applications for in vivo diagnostics and drug delivery, stressing the importance of thoroughly investigating the biocompatibility of potentially translatable nanoparticles (NPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The best transfecting particles were those with lower F A . Tirelli and co-workers deeply investigated the possibility to use a hyaluronan coating on chitosan-TPP nano-gels [81,86,87,88,89]. They reported that hyaluronic acid coating reduced the immunogenity and toxicity of nano-gels [87,88,89].…”
Section: Ionic Chitosan Micro- and Nano-gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best transfecting particles were those with lower F A . Tirelli and co-workers deeply investigated the possibility to use a hyaluronan coating on chitosan-TPP nano-gels [81,86,87,88,89]. They reported that hyaluronic acid coating reduced the immunogenity and toxicity of nano-gels [87,88,89].…”
Section: Ionic Chitosan Micro- and Nano-gelsmentioning
confidence: 99%
“…Tirelli and co-workers deeply investigated the possibility to use a hyaluronan coating on chitosan-TPP nano-gels [81,86,87,88,89]. They reported that hyaluronic acid coating reduced the immunogenity and toxicity of nano-gels [87,88,89]. Almalik et al provided evidence that CD44-mediated endocytosis was responsible for the uptake of materials where HA was used as the coating agent [81,90].…”
Section: Ionic Chitosan Micro- and Nano-gelsmentioning
confidence: 99%
“…Chitosan (CS) as a biocompatible, biodegradable, and nontoxic polymer has been under various investigations for the fabrication of the HA-coated NPs using the IG method. [18,19]. Thereafter, MT was encapsulated into the hydrophobic core of the nanoparticle containing a disulfide bond of Lipoic acid (LA) utilized as a reduction part [20].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reactive oxygen species (ROS) production was suppressed when activated macrophages were treated with HA modified chitosan nanoparticles. The secretion of cytokines such as TNF-α and IL-1β were drastically reduced, indicating low immunogenicity of the HA-CS NPs without any collateral biological responses [51]. Zaki et al also demonstrated that HA-chitosan NPs were taken up at a relatively slower rate compared to NPs not coated with HA.…”
Section: Immunogenicity Of Ha-based Nanoparticlesmentioning
confidence: 99%